Akurasi Pengukuran kWh Meter Analog Terhadap Losses Energi Listrik - Alfi Novri Waldi (Sutet, 2021)
Every measurement of electrical energy has a vital and very decisive role. Kilo Watt Hour (kWh) meter is an equipment used to measure a value or price of electricity usage (watt hour) in the period of time used. The problem of losses that occur in the kWh Meter is one of the problems. The problem faced is how to make readings and measurements of the use of electricity measured properly. In this study, the objectives to be achieved are to find out when the kWh meter deviation calculation shows results of no more than the permissible kWh deviation tolerance, namely -2% and +2% results and to correct electrical energy losses, ranging from technical and non-technical kWh meter errors. technical. Based on the results of research conducted using manual calculations and using special software. With the software makes it easier for studies to be carried out. In this case, it is the non-technical determination of kWh that usually accounts for the biggest losses, because this is not 100% pure damage from the kWh Meter, but there are PLN Consumers who are not responsible for the losses given. From the results of technical testing of the 3 kWh Meter which obtained data and specifications up to the deviation of the kWh Meter and from the results of studies conducted on non-technical testing, it turns out that this is what contributes to losses on a large scale.